AWARENESS ON BANK OF THE PHILIPPINES ISLANDS EXPRESS ASSIST RELATIVE TO BANKING TRANSACTIONS CONVENIENCE - Gonzales, S. Joshua; Jonalie T. Obillo; Verlyn M. Ocon; Hector R. Rubiales II (2015)
This study aimed to know the level of awareness on Bank of the Philippine Islands Express Assist (BEA). The subject of the study was the Bank of the Philippine Islands located in San Mateo, Rizal represented by 100 respondents experienced using Bank of the Philippine Islands Express Assist. The respondents were randomly selected. Descriptive Method of research was utilized in this study in order to present important information about Bank of the Philippine Islands Express Assist (BEA). For better result and accuracy of interpretation of the gathered data, the researchers used Statistical treatment, the Frequency and Percentage Distribution, and ranking were used to determine the profile of the respondents in terms of number of times in using BEA. To know the evaluation of the level of awareness of respondents on Bank of the Philippine Islands Express Assist of BPI in providing convenient banking experience, weighted mean was utilized. For the significant difference on the difference on the profile and assessment or BEA, One-way ANOVA was applied.
Undergraduate Thesis